Competitiveness and interest rates : the case of investing in new housing in Poland in 2002-2010 - Zenka-Podlaszewska, Dominika (Economics and Business Review, 2012)
The purpose of the paper is to examine the existence of a long-term relationship between interest rates on housing loans (mortgage rates) and investment in different forms of new housing in the years 2002-2010, along with competitiveness of those different forms of investing. This paper contains an empirical study using co-integration and impulse response analyses. A definition of competitiveness is introduced and discussed. The main trends in the number of newly completed housing units (broken down by type of investor) and interest rates in Poland are presented. Only competitive forms of investments have a long-term relationship with the interest rate in the Polish zlotys. (original abstract)